Association between dietary inflammation index and herpes simplex virus I and II: A cross-sectional study - Jing Luo; En-Hui Liu; Hao-Kai Chen; Xiang-Ping He; Tong Chen; Yu-Qi Hu; Xu-Guang Guo (PLoS ONE, 2025)
Introduction We aimed to fill the research gap between DII and herpes simplex virus infection among adults in the US by analyzing the association between dietary inflammatory index and herpes simplex virus and to provide new ideas for herpes simplex virus prevention and treatment. Method We used data from 8636 participants in NHANES 2007–2016, which were statistically analyzed by participant baseline study, one-way analysis of variance, multiple regression equations, smoothed curve fitting, and stratified analysis. Result In the fully adjusted model, the DII high concentration group was positively associated with the prevalence of herpes simplex (1.15 (0.89, 1.48), p = 0.0027), and the results of the stratified analyses indicated that the positive association between DII and herpes simplex virus type II was stable in the population. Conclusion This study demonstrates a positive association between DII and herpes simplex virus II in US adults, suggesting that a proinflammatory diet may be an independent risk factor for herpes simplex virus II.